The Role of Allotments and Community Gardens and the Challenges Facing Their Development in Urban Environments—A Literature Review - Anita Kwartnik-Pruc; Gabriela Droj (Land, 2023)
Current research largely focuses on the role of allotment gardens, the challenges facing them, and the direction of their future development in urban environments. The main idea behind the introduction of allotment gardens was to improve the living conditions and food supply of workers and the underprivileged. The impact of allotment gardening does not only concern the allotment gardeners but also the general public and the environment. It is important to emphasise that allotments have impacts not only on food production and outdoor physical activity, but also on the reuse of idle or neglected land, community development, therapeutic and nutritional benefits, and psychological benefits for allotment holders and residents. For this reason, this study captures six broad themes related to allotments: (1) community participation and cohesion, (2) health and well-being, (3) economic opportunities, (4) pollution, (5) urban planning and development, and (6) sustainable environment. The research is a systematic review in which steps were taken to minimise bias in the identification, selection, and summarisation of studies. The initial literature selection was based on a keyword search (title, abstract, and keywords) of the comprehensive literature databases Web of Science (all years) and Scopus (all years). The total scientific literature on which this review is based includes 162 research articles published between 1978 and July 2022. This work aims to fill these gaps and analyse existing knowledge by providing a detailed review of the academic literature, focusing not only on the benefits of community gardens and allotments in urban areas, but also on the existing problems related to allotments and urban gardening. Possible directions of development are also analysed based on the legal regulations in each country.